How accurate do markets predict the outcome of an event? The Euro 2000 soccer championships experiment - Carsten Schmidt; Axel Werwatz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
For the Euro 2000 Soccer Championships an experimental asset market was condueted, with traders buying and selling contracts on the winners of individual matches. Market-generated probabilities are compared to professional bet quotas, and factors that are responsible for the quality of the market prognosis are identified. The comparison shows, that the market is more accurate than the random predictor and slightly better than professional bet quotas, in the sense of mean square error. Moreover, the more certain the market predicts the outcome of an event the more accurate is the prediction.
urn:nbn:de:kobv:11-10048875
Keywords: C93; D4; G1; 330; experimental asset markets; prognosis; market efficiency